A Cross-National Comparative Analysis of Destination Satisfaction and Loyalty Between Chinese and Australian Independent Tourists: A Study of Phuket - Promsivapallop, Pornpisanu (Animo Repository, 2018)
This study primarily aims to offer a comparative analysis of destination satisfaction across two nationalities of international tourists, namely Chinese and Australians, on their holiday experience in Phuket. The results are drawn from 259 Chinese and 277 Australian independent tourists. The findings illustrate more differences than similarities in terms of destination satisfaction between the two nationalities. The Chinese tourists were found to be less satisfied with most aspects of their holiday, as compared to the Australian tourists, although no differences were detected in their destination loyalty. In addition, destination loyalty was found to be influenced by the satisfaction of accommodation and safety, and the quality of beaches.